2009
DOI: 10.1177/175114370901000218
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Accuracy of Death Certification on the Intensive Care Unit and the Proposed Reforms to the Coroner's System

Abstract: The requirement for the certification of death in the United Kingdom (UK) is currently undergoing unprecedented change, partly because of the Shipman Inquiry. Doctors undergo little training in completion of death certificates and inaccuracies can therefore arise. This survey compares the causes of death of 30 patients as cited by trainees, consultant intensivists and a consultant pathologist in one intensive care unit. We also review the changes in death certification that may be instituted as a result of pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 6 publications
0
12
0
1
Order By: Relevance
“…Deficiencies with death certification in the UK have been highlighted previously in the earliest confidential enquiry into perioperative deaths and problems remain. 19 The use of death certification is retrospective, identifies mortality but not morbidity, relies on accurate certification data, and analysis of individual cases is problematic. In this project, we chose a prospective methodology with a system of local reporters to identify cases.…”
Section: Discussionmentioning
confidence: 99%
“…Deficiencies with death certification in the UK have been highlighted previously in the earliest confidential enquiry into perioperative deaths and problems remain. 19 The use of death certification is retrospective, identifies mortality but not morbidity, relies on accurate certification data, and analysis of individual cases is problematic. In this project, we chose a prospective methodology with a system of local reporters to identify cases.…”
Section: Discussionmentioning
confidence: 99%
“…This is similar to findings in a study by Tuffin et al that showed that majority of death certificates were completed by junior doctors. 3 In their study they concluded that "junior doctors rarely receive formal training in the completion of MCCDs; nor is knowledge of the correct procedures involved in completing a MCCD required for competency based training in any of the four hospital specialties audited". 3 This they believe accounted for the high rate of errors.…”
Section: Discussionmentioning
confidence: 99%
“…3 In their study they concluded that "junior doctors rarely receive formal training in the completion of MCCDs; nor is knowledge of the correct procedures involved in completing a MCCD required for competency based training in any of the four hospital specialties audited". 3 This they believe accounted for the high rate of errors. The same situation pertains in our setting where there is little structured teaching on the completion of MCCDs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations